2019
DOI: 10.2528/pierc19020202
|View full text |Cite
|
Sign up to set email alerts
|

Merr Inspired CPW Fed SSGF Antenna for Multiband Operations

Abstract: An Electric Ring Resonator (ERR) loaded Sierpinski Square Gasket Fractal (SSGF) antenna for multiple frequency band application is proposed, fabricated, and measured. The CPW-fed antenna consists of a Multi-mode Electric Ring Resonator (MERR) which is fixed on reverse side of the substrate and iterated Sierpinski gasket fractal derived from a square patch which is stamped on top of an FR4. Multi-bands can be obtained by placing a single multi-mode ERR beneath the CPW structure of the antenna. Each resonating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Fractal antennas development recommend today for their use in ultra-and super-high frequency bands. Among them, the Sierpinski fractal proved its ability to solve interesting applications (9)(10)(11)(12)(13)(14) and may also be used for remote vital signs sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal antennas development recommend today for their use in ultra-and super-high frequency bands. Among them, the Sierpinski fractal proved its ability to solve interesting applications (9)(10)(11)(12)(13)(14) and may also be used for remote vital signs sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, much effort has been made in the development of flexible/wearable antennas with notch properties, and a variety of notch techniques have been adopted, such as etching various shaped slot on the radiating patch 11 17 or ground plane incorporation of electric ring resonator (ERR) 18 , split ring resonators (SRRs) 11 , 19 22 or complementary split ring resonators (CSRRs) 23 26 , using parasitic elements 27 , 28 , defected ground structures (DGS) 29 31 and EBG resonators 32 35 , etc. For instance, Geyikoglu et al 29 demonstrated the design and implementation of a flexible UWB antenna with dual-band rejection capabilities for wearable biomedical devices.…”
Section: Introductionmentioning
confidence: 99%